Vital sign monitoring following stroke associated with 90-day independence: A secondary analysis of the QASC cluster randomized trial. (January 2019) - Middleton, Sandy; McElduff, Patrick; Drury, Peta; D'Este, Catherine; Cadilhac, Dominique A.; Dale, Simeon; Grimshaw, Jeremy M.; Ward, Jeanette; Quinn, Clare; Cheung, N. Wah; Levi, Chris
Abstract: Background: The Quality in Acute Stroke Care Trial implemented nurse-initiated protocols to manage fever, hyperglycaemia and swallowing (Fever, Sugar, Swallow clinical protocols) achieving a 16% absolute improvement in death and dependency 90-day post-stroke. Objective: To examine associations between 90-day death and dependency, and monitoring and treatment processes of in-hospital nursing stroke care targeted in the trial. Design: Secondary data analysis from a single-blind cluster randomised control trial. Setting: 19 acute stroke units in New South Wales, Australia. Participants: English-speakers ≥18 years with ischaemic stroke or intracerebral haemorrhage arriving at participating stroke units <48 h of stroke onset, excluding those for palliation and without a telephone. Method: Data from patients in the 10 intervention hospitals and the nine control hospitals in the QASC trial post-intervention cohort, who had both hospital process of care data and 90-day outcome data were included. Associations between independence at 90-day (modified Rankin Score ≤1) and processes of care for fever, hyperglycaemia, and dysphagia screening were examined using multiple logistic regression adjusting for treatment group, sex, age group, premorbid modified Rankin scale, marital status, education, stroke severity and correlation within hospitals. Results: Of 1126 patients in the post-intervention cohort (intervention or control), 970 had both in-hospital processes of care data and 90-day outcome data. Patients had significantly lower odds of 90-day independence if, within the first 72 h of stroke unit admission, they had one or more: febrile event (≥37.5 °C) (OR 0.47; 95%CI:0.35-0.61; P < 0.0001), higher mean temperature (OR:0.25; 95%CI:0.14-0.45; P < 0.0001), finger-prick blood glucose reading ≥11 mmol/L (OR:0.61; 95%CI:0.47-0.79; P = 0.0002), higher mean blood glucose (OR 0.89; 95%CI:0.84-0.95; P = 0.0006), or failed the swallowing screen (OR 0.35; 95%CI:0.22-0.56; P < 0.0001). Patients had greater odds of independence when: venous blood glucose was taken on admission to hospital or within 2 h of stroke unit admission (OR 1.4; 95%CI:1.01–1.83; P = 0.04); finger-prick blood glucose was measured within 72 h of stroke unit admission (OR 1.3; 95%CI:1.02-1.55; P = 0.03); or when swallowing screening or assessment was performed within 24 h of stroke unit admission (OR 1.8; 95%CI:1.29-2.55; P = 0.0006). Conclusion: We have provided robust evidence of the importance of monitoring patients' temperature, blood glucose and swallowing status to improve 90-day stroke outcomes. Routine nursing care can result in significant reduction in death and dependency post-stroke.